(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Non-return valve is a critical component in fluid mechanics and mechatronic systems, ensuring unidirectional flow while preventing backflow, which is essential for system efficiency and safety. These valves are widely used in hydraulic, pneumatic, and process control systems, playing a vital role in preventing pressure surges, cavitation, and mechanical failure. Understanding the fluid dynamics behavior inside a non-return valve is essential for optimizing its design and performance. However, due to the complex flow interactions within the valve, analytical solutions are often insufficient, necessitating numerical simulations for accurate analysis. This study presents a numerical simulation model of fluid flow through a non-return valve using Computational Fluid Dynamics (CFD) techniques. The primary objective is to provide an integrated learning approach that enhances students' and engineers' understanding of the interaction between fluid flow and valve dynamics. The research employs CFD simulations to visualize pressure distributions, velocity profiles, and turbulence effects under different flow conditions, offering insights into the valve’s operational characteristics. The methodology includes Theoretical background on valve mechanics and fundamental fluid flow equations; Numerical modeling using ANSYS Fluent, where the valve geometry, boundary conditions, and turbulence models are defined; Simulation and analysis of pressure drop, velocity distribution, and flow separation within the valve. The results highlight how flow conditions influence valve efficiency, showing pressure losses, cavitation risks, and flow separation effects. The study demonstrates that numerical simulations provide a powerful tool for engineering education, allowing students to visualize complex flow behaviors and develop practical skills in CFD analysis. By integrating simulation-based learning into engineering curricula, this approach strengthens problem-solving abilities and prepares future engineers for real-world challenges in fluid mechanics and mechatronics.